2023
DOI: 10.47115/bsagriculture.1311020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Calving Season and Specific Gravity of First Milking Colostrum on Milk Components and Somatic Cell Count in Early Lactation Anatolian Buffalo (Bubalus bubalis) Cows

Hüseyin ERDEM,
İbrahim Cihangir OKUYUCU,
Hasan DEMİRCİ

Abstract: This study aimed to evaluate the milk components and somatic cell count (SCC) of Anatolian buffalo cows at different stages of lactation (days 15th, 30th, 45th and 60th of lactation) by determining the effects of the age of the cow, calving season and specific gravity of colostrum (SGC) on these milk quality traits. The experiment was conducted using 62 healthy lactating primiparous and multiparous Anatolian buffalo cows at two private farms in Samsun, Turkey. The SGC values at the second hour (first milking) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…In addition, Antanaitis et al [ 30 ] noted that older Holstein cows have a calmer milking temperament compared to younger cows. The impact of parity on quantitative−qualitative milk parameters was quite variable, as observed in the literature; Verma et al [ 49 ] did not determine significant changes in these parameters, as in our study, while others observed an increase in milk components and milk yield [ 50 , 51 ]. The efficiency of the milking process in buffaloes is more affected by anatomical factors, especially teat morphology [ 26 ], and physiological differences are found between these species than between dairy cattle [ 43 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 77%
“…In addition, Antanaitis et al [ 30 ] noted that older Holstein cows have a calmer milking temperament compared to younger cows. The impact of parity on quantitative−qualitative milk parameters was quite variable, as observed in the literature; Verma et al [ 49 ] did not determine significant changes in these parameters, as in our study, while others observed an increase in milk components and milk yield [ 50 , 51 ]. The efficiency of the milking process in buffaloes is more affected by anatomical factors, especially teat morphology [ 26 ], and physiological differences are found between these species than between dairy cattle [ 43 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 77%